2011
DOI: 10.1007/s00348-011-1181-4
|View full text |Cite
|
Sign up to set email alerts
|

Local curvature measurements of a lean, partially premixed swirl-stabilised flame

Abstract: A swirl-stabilised, lean, partially premixed combustor operating at atmospheric conditions has been used to investigate the local curvature distributions in lifted, stable and thermoacoustically oscillating CH 4 -air partially premixed flames for bulk cold-flow Reynolds numbers of 15,000 and 23,000. Single-shot OH planar laser-induced fluorescence has been used to capture instantaneous images of these three different flame types. Use of binary thresholding to identify the reactant and product regions in the OH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 60 publications
2
28
0
1
Order By: Relevance
“…This observation indicates that the flame front curvature distributions are dominant by the large-scale structures and the effect of Kolmogorov-scale eddies are minimal. This observation is in agreement with previous measurements of Yuen and Gülder [87], whereas Kostiuk et al [86], Haq et al [77], Gashi et al [85], and Bayley et al [84] observed that the flame front curvature distribution becomes wider by increasing the turbulence intensity. It is observed that the flame front curvature distributions for lean/stoichiometric and rich mixtures are identical when the unstrained premixed laminar burning velocity, non-dimensional bulk flow velocity, non-dimensional turbulence intensity, and non-dimensional longitudinal integral length scale were kept constant, see, for example, Flames M9 and M16.…”
Section: Two-dimensional Local Flame Front Curvaturesupporting
confidence: 93%
See 2 more Smart Citations
“…This observation indicates that the flame front curvature distributions are dominant by the large-scale structures and the effect of Kolmogorov-scale eddies are minimal. This observation is in agreement with previous measurements of Yuen and Gülder [87], whereas Kostiuk et al [86], Haq et al [77], Gashi et al [85], and Bayley et al [84] observed that the flame front curvature distribution becomes wider by increasing the turbulence intensity. It is observed that the flame front curvature distributions for lean/stoichiometric and rich mixtures are identical when the unstrained premixed laminar burning velocity, non-dimensional bulk flow velocity, non-dimensional turbulence intensity, and non-dimensional longitudinal integral length scale were kept constant, see, for example, Flames M9 and M16.…”
Section: Two-dimensional Local Flame Front Curvaturesupporting
confidence: 93%
“…These distributions are observed to be Gaussian, and they are symmetrical about zero flame front curvature. Similar observations were previously reported in the literature for premixed turbulent Bunsen flames, see, for example, [34,[53][54][55]73,80,81], premixed turbulent low-swirl stabilized flames, see, for example, [62,82,83], partially premixed turbulent low-swirl stabilized flames, see, for example, [84], premixed turbulent propagating flame kernels, see, for example, [77,85], premixed turbulent V-shaped flames, see, for example, [36], and premixed turbulent opposed streams, see, for example, [86]. It is observed that the standard deviation of the distributions does not change with increasing equivalence ratio, see, for example, Flames E1-E8.…”
Section: Two-dimensional Local Flame Front Curvaturesupporting
confidence: 90%
See 1 more Smart Citation
“…The extracted contours were then represented parametrically in Cartesian coordinates, x(s) and y(s), as a function 14 of the path length parameter, s, of the contour and all subsequent flame contour quantities such as flame front normals and flame front curvatures, , were calculated from the parameterized contours. We used the processing procedure described in [41] for the extraction of the flame curvature, which results in the error of the local curvature value being within 10%.…”
Section: Conditioned Particle Image Velocimetrymentioning
confidence: 99%
“…Some traditional methods usually use edge detection operators [2], [8] to detect flame front. They always have the problems of low efficiency for noisy flame images and still suffer from the difficulties of determining the suitable global or local thresholds from intensity inhomogeneous images.…”
Section: Introductionmentioning
confidence: 99%